Evaluation method for deep-source CO2 tracer mineral formation process

By analyzing the occurrence characteristics and dynamic changes of CO2 tracer minerals using petrological and geochemical methods, this study solves the problem of systematic and accurate analysis of the formation process of CO2 tracer minerals in existing technologies, and enables precise evaluation of reservoir pore structure and permeability characteristics, supporting reservoir distribution prediction and CO2 sequestration safety assessment.

CN121439016APending Publication Date: 2026-01-30CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511486628.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-01-30

AI Technical Summary

Technical Problem

Existing technologies are insufficient for systematically and accurately analyzing the formation process of CO2 tracer minerals and cannot accurately evaluate the impact of CO2 on reservoir pore structure and permeability characteristics, thus affecting the prediction of oil and gas accumulation and migration.

Method used

Using petrological testing methods and geochemical analysis, combined with carbon, oxygen, and strontium isotope testing, and through thin section observation, XRD clay mineral diffraction, and scanning electron microscopy, the occurrence characteristics of CO2 tracer minerals were systematically characterized, the formation period and carbon source properties were determined, and the dynamic change process of CO2 tracer minerals was simulated using geochemical simulation software.

Benefits of technology

It enables systematic and quantitative analysis of the formation process of CO2 tracer minerals, accurately evaluates the impact of CO2 on reservoir pore structure and permeability, provides a scientific basis for predicting the distribution of high-quality reservoirs and assessing the safety of CO2 storage, and is applicable to different regions and reservoir conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121439016A_ABST
    Figure CN121439016A_ABST
Patent Text Reader

Abstract

The invention discloses an evaluation method for a deep-source CO2 tracer mineral formation process, and belongs to the field of petroleum and natural gas geology. According to the method, firstly, the occurrence characteristics and the formation time sequence of the deep-source CO2 tracer mineral are represented through a petrology testing system; further utilizing geochemical tests of carbon, oxygen and strontium isotopes, trace elements and the like to judge the carbon source property and cause background; on the basis, the time-space distribution rule, the time sequence relation and the cause background of the minerals are synthesized, the charging period of the CO2 fluid is divided, and the charging rule is clarified; further, determining a charging time window of the carbon source fluid in combination with a geochemical method; and finally, geochemical simulation software is utilized to construct a reservoir model based on the filling time, and the formation process of minerals under different periods of fluid filling is dynamically simulated. According to the invention, systematic and dynamic evaluation of the deep CO2 fluid migration-precipitation history is realized, and key technical support is provided for research of oil and gas accumulation, carbon sequestration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of petroleum and natural gas geology, and particularly relates to a method for evaluating formation process of deep-source CO2 tracer mineral. BACKGROUND

[0002] In recent years, carbon dioxide (CO2) geological storage technology has been widely studied in oil and gas reservoirs and deep water layers as an important means to address greenhouse gas emissions. During the CO2 injection process, reservoir minerals react with CO2, which may lead to the dissolution of unstable aluminosilicate minerals and the generation of carbonate minerals, and change the pore structure and permeability of the reservoir, directly affecting the storage and migration of oil and gas. Carbonate minerals such as davyne, ankerite and iron calcite often occur in clastic rock reservoirs that were filled with CO2-rich fluids during geological history, and are considered as CO2 migration and reaction tracer minerals, but the formation period and material source of different carbonate minerals may differ. The existing analysis method for the formation process of CO2 tracer minerals mainly relies on mineralogical observation and isotope analysis, which can qualitatively or semi-quantitatively evaluate the mineral types and existing states.

[0003] Therefore, there is a need for a method for systematic, accurate and dynamic analysis of CO2 tracer minerals in clastic rock reservoirs, which can accurately evaluate the final impact of CO2 on the pore structure and permeability of the reservoir, and provide a scientific basis for predicting the distribution of high-quality reservoirs and evaluating the long-term safety of CO2 storage. SUMMARY

[0004] In view of the above problems, the present application provides a method for evaluating the formation process of deep-source CO2 tracer minerals, which can comprehensively evaluate the formation process of CO2 tracer minerals.

[0005] The technical scheme of the present application is as follows:

[0006] A method for evaluating the formation process of deep-source CO2 tracer minerals, comprising:

[0007] S1, using petrological testing methods, systematically characterizing the occurrence characteristics of different deep-source CO2 tracer minerals in the reservoir of the study area, determining the formation period of the CO2 tracer minerals, and inferring the time sequence relationship according to the occurrence characteristics; S2, based on the CO2 tracer minerals in S1, using carbon, oxygen and strontium isotope tests to clarify the elemental geochemical characteristics of different period CO2 tracer minerals, and to identify their carbon source properties and genetic background; S3, by analyzing the vertical and horizontal distribution rules and geochemical characteristics of different CO2 tracer minerals, and combining the time sequence relationship of S1 and the genetic background of S2 for calibration, the CO2 tracer mineral fluid charging period and range are divided; S4, based on the divided fluid filling period, using geochemical methods, and matching the analysis results with regional tectonic characteristics and events, so as to determine the carbon source fluid filling time window of the CO2 tracer mineral in the study area; S5, using geochemical simulation software, based on the carbon source fluid filling time, constructing a corresponding dense sandstone reservoir model in the study area, and simulating the dynamic change process of different CO2 tracer minerals under different period carbon source fluid filling conditions.

[0008] Further, the petrological test method comprises one or more of thin section observation, XRD clay mineral diffraction, scanning electron microscopy and cathodoluminescence analysis.

[0009] Further, the geochemical characteristics are obtained by micro-area microelement test.

[0010] Further, the carbon, oxygen and strontium isotope test specifically comprises: using a stable isotope mass spectrometer to test the carbon and oxygen sources of the CO2 tracer mineral.

[0011] Further, the discrimination mode of the genetic background is calculated by CO2-calcite / bikita fractionation coefficient.

[0012] Further, the geochemical method comprises one or more of fluid inclusion homogenization temperature analysis and stratigraphic thermal burial history reconstruction method.

[0013] Further, the geochemical simulation software uses Geochemist's Workbench.

[0014] The beneficial effects of the present application include:

[0015] 1. The present application provides a system, quantitative, multi-dimensional coupling method, which can accurately identify the formation process of deep source CO2 tracer mineral, convert the static record of mineralogy into dynamic model of pore evolution, accurately evaluate the final influence of CO2 on reservoir pore structure and permeability characteristics, and provide scientific basis for predicting high-quality reservoir distribution and evaluating long-term safety of CO2 storage.

[0016] 2. The evaluation method provided by the present application can be combined with geochemical simulation software, and is suitable for genetic analysis and prediction of deep source CO2 tracer mineral in different regions and different reservoir conditions, and has good universality. BRIEF DESCRIPTION OF DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed to be used in the embodiments or prior art description will be briefly introduced. Obviously, the drawings in the following description only constitute some embodiments of the present application, and for those skilled in the art, other drawings can be obtained based on these drawings without creative labor.

[0018] Figure 1 is a method flow chart of the present application;

[0019] Figure 2 is the occurrence characteristic of type I davyne;

[0020] Figure 3 is the occurrence characteristic of type II davyne;

[0021] Figure 4 is the occurrence characteristic of type III davyne;

[0022] Figure 5 Comparison of CO2 carbon isotopes of davyne with inorganic / organic origin CO2 carbon isotopes;

[0023] Figure 6 is the simulation reaction of the injection stage of the first CO2 injection cycle;

[0024] Figure 7 is the simulation reaction of the formation reaction stage of the first CO2 injection cycle;

[0025] Figure 8 is the simulation reaction of the injection stage of the second CO2 injection cycle;

[0026] Figure 9 is the simulation reaction of the formation reaction stage of the second CO2 injection cycle;

[0027] Figure 10 is the simulation reaction of the injection stage of the third CO2 injection cycle;

[0028] Figure 11 is the simulation reaction of the formation reaction stage of the third CO2 injection cycle;

[0029] Figure 12 is the PAAS standardization mode chart of type I davyne;

[0030] Figure 13 is the PAAS standardization mode chart of type II davyne;

[0031] Figure 14 is the PAAS standardization mode chart of type III davyne. DETAILED DESCRIPTION

[0032] The present application will be described below in conjunction with the drawings Figures 1 to 14The technical solutions in the embodiments of the present application are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.

[0033] Embodiments

[0034] For a long time, domestic and foreign scholars have taken dawsonite, NaAlCO3(OH)2, as a tracer mineral for large-scale migration, aggregation or escape of CO2. In this embodiment, the application of the evaluation method of the formation process of deep source CO2 tracer minerals to the Fuyu oil layer in the southern Songliao Basin is further illustrated by taking dawsonite as an example.

[0035] S1, through petrological test method, the occurrence characteristics of different deep source CO2 tracer minerals in the reservoir are systematically characterized, the formation period of the CO2 tracer mineral is determined, and the time sequence is inferred according to the occurrence characteristics:

[0036] In this embodiment, the petrological test method adopts thin section observation, XRD clay mineral diffraction and scanning electron microscope observation. The thin section is an orthogonal polarized observation thin section. The XRD clay mineral diffraction uses a Japan Rigaku SmartLab-9kWX X-ray diffractometer with a Cu target (λ=0.15406 nm), a Ni filter, a tube pressure of 45 kV, a tube flow of 200 mA, continuous scanning, 3-70° (2θ), a step of 0.02° (2θ), and a scanning speed of 10° / min. The scanning electron microscope is a SEM, JSM-6700 type. The observation results show that the dawsonite developed in the fourth member of the Quantou Formation in the southern Songliao Basin has various occurrences, and the crystal morphology has obvious differences, showing hair-like (type I), needle-like (type II) and fine strip-like (type III). The quartz and ankerite associated with the three types of dawsonite have no obvious crystal morphology characteristics. The iron calcite and ankerite are mostly subhedral or euhedral crystals filling intergranular pores or dissolution pores, or replacing detrital particles (quartz, feldspar or rock debris). In addition, the ankerite can be seen to wrap or partially replace the iron calcite. Therefore, it can be known that the ankerite is formed later than the iron calcite:

[0037] Type I dawsonite (hair-like): Type I dawsonite has first-order gray, yellow and orange interference colors under orthogonal light, fills intergranular and intragranular pores in clusters, has directionality, partially replaces quartz, feldspar and rock debris, and is often associated with ankerite and authigenic quartz. Figure 2 ).

[0038] Type II dawsonite (needle-like): Type II dawsonite has first-order gray, yellow and orange interference colors to second-order blue under orthogonal light, clusters are often radially divergent outward, have directionality, partially replace quartz, feldspar and rock debris, and are often associated with ankerite and authigenic quartz, and occasionally associated with iron calcite. Figure 3 ).

[0039] Type III daphnite (thin platelets): under orthogonal light, interference colors are first-order white, second-order yellow, and blue. Type III daphnite single crystals have clear boundaries and extend outward in the form of platelets. Daphnite clusters fill intergranular pores in a radial manner and have a directional property. Some quartz, feldspar, and rock debris are partially replaced, and the content is relatively small Figure 4 ).

[0040] S2, based on the CO2 tracer mineral in S1, use carbon, oxygen, and strontium isotope tests to clarify the elemental geochemical characteristics of different periods of CO2 tracer minerals and identify their carbon source types and genetic backgrounds:

[0041] Inorganic CO2 charging occurred in the geological history of the southern Songliao Basin, and multiple inorganic CO2 gas reservoirs were discovered in the shallow layer. In this embodiment, 14 sandstone samples containing no organic matter were selected, and oxygen, carbon, and strontium isotopes of the carbonate cement were analyzed. About 60 milligrams of powder sample was extracted for strontium isotope analysis.

[0042] The results show that the δ 13 C value of daphnite ranges from -3.8‰ to -0.8‰, which is consistent with the δ 13 C value distribution range of daphnite formed by mantle-derived-magmatic CO2 confirmed at home and abroad (the δ 13 C value of daphnite in the Bowen-Gunnedah-Sydney (BGS) basin in Australia ranges from -4‰ to 4.1‰; the δ 13 C value of daphnite in the southern Songliao Basin ranges from -4.97‰ to 3.29‰).

[0043] In addition, to further determine the source of carbon elements in the carbonate cement in the study area, the carbon isotope values (δ 13 CCO2) of CO2 gas in equilibrium with daphnite, ankerite, and iron calcite carbonate cements were calculated in this embodiment. The calcite-carbon dioxide fractionation coefficient was used as the fractionation coefficient of carbonate cements-carbon dioxide at the same temperature, and the calcite-carbon dioxide fractionation equation was used for calculation (Ohmoto, 1979; Baker et al., 1995).

[0044] The calculation results (Table 1) show that the carbon isotope of CO2 gas in equilibrium with daphnite in the reservoir of the Quan four member in the CO2 charging area ranges from -9.83‰ to -6.9‰ (PDB), with an average of -8.17‰. According to the CO2 gas reservoir genetic classification proposed by Dai Jinxing in eastern China, the carbon isotope (δ 13CO2 (carbon dioxide) is mainly distributed in the range of -8‰ to +3‰. Organically derived CO2 is less than -10‰, while when CO2 is between -10‰ and -8‰, it is of mixed origin, consisting of inorganic and organic CO2. Among inorganically derived CO2, the δ¹⁸O of carbon dioxide from carbonate metamorphic rocks... 13 The CCO2 value is close to that of carbonate rocks. 13 The C value is approximately 0 ± 3‰, while the δ¹⁴C value for mantle-derived magmatic carbon dioxide is... 13 CCO2 values ​​are mostly between -6% and ±2%. The δ¹⁸O values ​​of CO2 in isotopic equilibrium with diatomite are... 13 C value (δ) 13 Half of the CO2 falls within the inorganic CO2 range (> -8‰), and the other half falls within the mixed range of inorganic and organic CO2 (-8‰ ~ -10‰), indicating that the source of CO2 is a mixture of organic and inorganic. Figure 5 ).

[0045] According to the above standards, the δ-type of diaspores formed in the Fuyu oil layer of the CO2-charged area... 13 The CCO2 value falls within the carbon isotopic range of mantle-magmatic CO2. However, due to the selection of the calculation formula, the fractionation coefficient of calcite-carbon dioxide was equated to that of pyrope-carbon dioxide at the same temperature. Furthermore, the sample selected for isotopic testing contained a small amount of ferroalloy, and some of this ferroalloy may have been formed with the participation of organic carbon, thus affecting the δ¹⁴ CCO2 value of pyrope. 13 The C value is relatively negative, which makes the final calculated δ 13 The CCO2 value is slightly negative. This indicates that the carbon in the diatomite in the Quan 4 Member reservoir, an inorganic CO2-filled area in the study area, mainly originates from mantle-derived magmatic CO2.

[0046] Strontium was separated using conventional cation exchange technology, and further separated using ion exchange technology. The determination was performed using a Neptune multi-collector inductively coupled plasma mass spectrometer (ICP-MS). 87 Sr / 86 Sr isotope ratio. Sr isotope analysis revealed that: [The following is a partial translation of the original text, which is incomplete and requires further context.] 87 Sr / 86 The Sr ratios (0.710996 and 0.712472, average 0.711720; Table 1) are much lower than the average of the upper continental crust. 87 Sr / 86 The Sr value (0.720±0.005) is slightly lower than the average for contemporaneous lacustrine limestone, but higher than the average for the mantle. Petrological analysis indicates a lack of clastic carbonate grains and bioclastic debris in the Quan 4 Member sandstone, suggesting the absence of an internal inorganic carbon source. The soda ash content is relatively low. 87 Sr / 86The Sr ratios indicate that the inorganic CO2 influx has contributions from both mantle and crustal sources.

[0047] The test results are based on the National Institute of Standards and Technology Standard Reference Material "987" solution, and the measurement accuracy of the results is ± 0.007‰.

[0048] The CO2 source related to the formation of davisite in the study area is the mixture of mantle-derived alkaline magma and crust-derived CO2, accompanied by a small amount of organic CO2 from organic matter, rather than pure mantle-derived CO2. The recharge area in the study area is located near the Gudian fault (<7.8 km), which connects the deep magma chamber and the shallow strata, providing a migration channel for mantle-derived alkaline magma CO2 and crust-derived CO2.

[0049] The δ 13 C and δ 18 O values of the iron dolomite in the normal zone sandstone are -2.3‰ VPDB and -18.3‰ VPDB, respectively, which are lower than those of the davisite. 87 Sr / 86 The Sr / Sr ratio is 0.712448. The δ 13 C values of the ankerite in the normal zone sandstone range from -4.5‰ to -10.5‰ VPDB, the δ 18 O values range from -19.3‰ to -14.9‰ VPDB, and the 87 Sr / 86 Sr ratio ranges from 0.712060 to 0.714030. The δ 13 C values of the ankerite in the recharge zone sandstone range from -5.7‰ to -2.6‰, the δ 18 O values range from -20.5‰ to -17.9‰ VPDB. The 87 Sr / 86 Sr ratios of davisite and ankerite range from 0.710216 to 0.712472.

[0050] The δ 13 C values of the ankerite in the recharge zone sandstone sandstone containing davisite range from -5.7‰ to -2.6‰ VPDB, which is comparable to the δ 13 C values of the davisite (-3.8‰ to -0.8‰). The calculated δ 13 CCO2 values of the ankerite (δ 13 CCO2) range from -11.56‰ to -8.52‰ (PDB) (average -9.99‰), mainly falling within the range of mixed inorganic and organic CO2 (-8‰ to -10‰; Dai et al., 1996). In addition, the 87 Sr / 86The Sr ratios (0.710216~0.711520, average 0.710791) are slightly lower than those of dawsonite (Table 1), which indicates that mantle-derived CO2 and crust-derived CO2 also participated in the formation of the ankerite.

[0051] The δ 13 C values of the normal zone sandstones are lower than those of the corresponding minerals in the infill zone. The δ 13 CCO2 values range from -16.66‰ to -8.08‰ (PDB) (average -11.68‰). According to the research of Dai Jinxing et al. (1996), the CO2 that caused the cementation of carbonates in the normal zone was mostly derived from organic matter (-10‰ to -26‰), which indicates that the decarboxylation of organic matter in the adjacent mudstone and the upper part of the Qingshankou Formation was the main carbon source for the normal zone sandstones.

[0052] The precipitation of dawsonite in the reservoir still requires the participation of Na + and Al 3+ ions. With the decrease of feldspar content, the dawsonite content gradually increases, that is, the dissolution of plagioclase and potassium feldspar can provide the metal ions required for the precipitation of dawsonite, and the reaction is as follows:

[0053] NaAlSi3O8+CO2+H2O→NaAlCO3(OH)2+3SiO2

[0054] KAlSi3O8+Na + +CO2+2H2O→NaAlCO3(OH)2+K + +3SiO2

[0055] S3, by analyzing the longitudinal and lateral distribution patterns and geochemical characteristics of different CO2 tracer minerals, combined with the time sequence of S1 and the genetic background of S2, the CO2 tracer mineral fluid infill stages and ranges are divided, and the infill law is elucidated:

[0056] Analysis of vertical and horizontal distribution regularity: thin section point counting method, scanning electron microscopy observation and analysis, whole rock X-ray diffraction analysis and other means were used to systematically characterize the samples in normal and injection areas. Some samples in the CO2 un-injected area were selected, which were close to the vertical depth and adjacent to the CO2 injection area. Through comparative analysis, the influence of CO2 injection on reservoir quality was clarified: the types of authigenic cements in the normal area were carbonate cement, quartz and clay minerals. The types of carbonate cement were iron calcite (0%-6.4%, average 1.1%) and iron dolomite (0%-18.8%, average 2.2%); the total amount of clay minerals was 6.3%-22.5%, with an average of 13.3%, and the main types of clay minerals were illite-smectite mixed layer (3.2%-12.8%, average 7.11%), chlorite (0.2%-6.3%, average 2.4%), kaolinite (1.2%-8.1%, average 2.6%) and illite (0.5%-4.6%, average 1.3%); the type of siliceous cement was mainly quartz secondary enlargement, with a content of 1.0%-2.5%, and an average of 1.6%; the types of authigenic mineral combination in the injection area were different from those in the normal area. The types of carbonate cement in the injection area were daphnite, iron dolomite and a small amount of iron calcite. Thin section point counting method analysis showed that the content of daphnite was 0.5%-10%, with an average of 4.8%; the content of iron dolomite was 0%-9%, with an average of 3.5%; the content of iron calcite was 0%-7%, with an average of 0.7%. Whole rock X-ray diffraction analysis showed that the total amount of clay minerals in the injection area was 9.3%-20.5%, with an average of 13.5%, and the main types were illite-smectite mixed layer (7.0%-16.8%, average 10.9%) and illite (1.1%-3.4%, average 2.4%), with a small amount of kaolinite (0%-1.2%, average 0.2%) and chlorite (0%-0.4%, average 0.07) basically not developed; the type of siliceous cement was mainly quartz secondary enlargement, with a content of 1.3%-3.3%, and an average of 2.5%.

[0057] Analysis of geochemical characteristics: micro-area microelement test was carried out on daphnite in the injection area (4 samples, 51 effective test points). NWR 193 HE laser ablation system of the laboratory was used, combined with Agilent 7900 single quadrupole inductively coupled plasma mass spectrometer. The complete isotope types determined included: 7 Li, 9 Be, 11 B, 23 Na, 25 Mg, 27 Al, 29 Si, 31 P, 39 K, 42 Ca, 45 Sc,47 Ti, 51 V, 53 Cr, 55 Mn, 57 Fe, 59 Co, 60 Ni, 63 Cu, 66 Zn, 71 Ga, 85 Rb, 88 Sr, 89 Y, 90 Zr, 93 Nb, 95 Mo, 133 Cs, 137 Ba, 139 La, 140 Ce, 141 Pr, 146 Nd, 147 Sm, 153 Eu, 157 Gd, 159 Tb, 163 Dy, 165 Ho, 166 Er, 169 Tm, 173 Yb, 175 Lu, 178 Hf, 181 Ta, 182 W, 208 Pb, 232 Th and 238 U. The ablation process of the samples was performed using helium as carrier gas. Each spot analysis consisted of about 20 s of background acquisition followed by 40 s of sample data acquisition. A 32 μm spot size was used with a repetition rate of 4 Hz and an energy density of about 2 J cm -2After analyzing 9-10 samples, several external reference materials were tested. This study used NIST 610 as a quality control (QC) reference material to correct the instrument's sensitivity drift over time, and selectively used multiple external standards (NIST 610, NIST 612, BCR-2G, BHVO-2G, and BIR-1G) for external calibration. Furthermore, aluminum was used as a uniform reference to correct for quality-dependent biases at each analytical point. The screening and integration of relevant isotope background information and analyte information, time drift correction, and quantitative calibration were all performed using ICPMSDataCal 10.9 software. The time-domain signal at each analytical point was rigorously verified during the testing process. The above testing methods and procedures were used to analyze and clarify the differences in trace elements among galvanites of different origins. Representative isotope test results are used for illustration: the Zr / Hf ratio of galvanites located in CO2-filled areas ranges from 11.51 to 152.5, with an average of 48.74, which is higher than the standard Zr / Hf ratio for chondrites (Zr / Hf=36; Sun and McDonough, 1989). Specifically, the Zr / Hf ratio of Type I galvanites (hair-like) ranges from 25.33 to 128.97, with an average of 47.42; the Zr / Hf ratio of Type II galvanites (acicular) ranges from 11.51 to 152.5, with an average of 53.29; and the Zr / Hf ratio of Type III galvanites (strip-like) ranges from 13.17 to 85.77, with an average of 40.49. The Y / Ho ratio ranges from 0.77 to 53.92, with an average of 19.59, which is lower than the standard Y / Ho ratio for chondrites (26–28; Bau and Dulski, 1995; Bau, 1996). Specifically, the Y / Ho ratio for Type I galvanite (hair-like) ranges from 6.28 to 53.9, with an average of 19.64; for Type II galvanite (acicular), it ranges from 4.32 to 53.92, with an average of 22.47; and for Type III galvanite (strip-like), it ranges from 0.76 to 34.97, with an average of 14.86. Rare earth element analysis shows that the total rare earth element (ΣREE) content of Type I galvanite (hair-like) ranges from (0.14 to 21.50) × 10⁻⁶. -6 The light rare earth element content (ΣLREE) is (0.04~20.19)×10 -6 2.96×10 -6 The heavy rare earth element content (ΣHREE) is (0.01~1.30)×10 -6 The average is 0.19×10 -6The ratio of light rare earth elements (ΣLREE / ΣHREE) ranged from 0.15 to 162.84, with an average of 27.96, showing an overall characteristic of high enrichment of light rare earth elements and severe depletion of heavy rare earth elements; the total rare earth element content (ΣREE) of type II diatomite (acicular) ranged from (0.01 to 2.69) × 10⁻⁶. -6 The light rare earth element content (ΣLREE) is (0.004~2.60)×10 -6 Average 0.30×10 -6 The heavy rare earth element content (ΣHREE) is (0.01~0.51)×10 -6 The average is 0.16×10 -6 The ratio of light rare earth elements (ΣLREE / ΣHREE) ranged from 0.04 to 31.75, with an average of 3.94, showing an overall characteristic of relative enrichment of light rare earth elements and depletion of heavy rare earth elements; the total rare earth element content (ΣREE) of type III scabra (fine slab-like) ranged from (0.08 to 3.44) × 10⁻⁶. -6 The light rare earth element content (ΣLREE) is (0.01~2.54)×10 -6 The average is 0.85×10 -6 The heavy rare earth element content (ΣHREE) is (0.03~0.90)×10 -6 The average is 0.26×10 -6 The ratio of light rare earth elements (ΣLREE / ΣHREE) ranges from 0.08 to 12.81, with an average of 3.47, showing an overall characteristic of relative enrichment in light rare earth elements and depletion in heavy rare earth elements. After normalization by the Australian Post-Archaeological Shale (PAAS), the distribution patterns of rare earth elements show significant differences: Type I diaspore exhibits a right-dipping LREE trend and a relatively flat HREE trend. Figure 12 The (La / Yb)N ratio ranges from 0.02 to 30.35 (mean 7.02), and the (La / Sm)N ratio ranges from 0.03 to 2.80 (mean 0.73), showing a positive Eu anomaly (δEu = 0.67–5.35, mean 1.94) and a slight negative Ce anomaly (δCe = 0.15–1.31, mean 0.71). Type II diatomite exhibits a left-sloping LREE trend and a HREE trend. Figure 13 The (La / Yb)N ratio is 0.01–0.15 (mean 0.05), and the (La / Sm)N ratio is 0.03–0.53 (mean 0.15), showing a slight negative Eu anomaly (δEu = 0.4–1.28, mean 0.95) and a slight positive Ce anomaly (δCe = 0.25–3.46, mean 1.06). Type III diatomite exhibits a left-sloping LREE trend and HREE trend (…). Figure 12), (La / Yb)N ratio is 0.22-0.26 (average 0.24), (La / Sm)N ratio is 0.03-1.57 (average 0.54), and shows Eu positive anomaly (δEu = 0.76-4.27, average 1.92) and slight negative anomaly of Ce (δCe = 0.02-1.47, average 0.84).

[0058] Combined with the timing of S1 and the genetic background of S2: petrological observation of S1 shows that the three kinds of davisite (type I hair-like, type II needle-like, type III fine lath-like) are orderly distributed: type I adheres to the edge of the grain and extends radially outward, and transitions to type II, and the outermost layer is type III, and there is no other mineral or hydrocarbon fluid between the three, and the timing is clear: type I→type II→type III. Calibration of this timing with geochemical characteristics shows that from early to late, the average of ΣREE decreases from 3.15×10 -6 to 0.45×10 -6 and then rises to 1.11×10 -6 , the LREE / HREE ratio decreases from 27.96 to 3.94 and 3.47, and the Eu and Ce anomaly characteristics change regularly. These systematic differences strictly correspond to the generation order. At the same time, the geochemical characteristics of all davisites remain consistent as a whole, indicating that the genetic background is deep-source inorganic CO2 recharge. Under this unified background, the differences in characteristics reflect the evolution of the properties of different period fluids.

[0059] Divide the CO2 tracer mineral fluid recharge period and clarify the recharge law: based on the above calibration, the three kinds of davisite with unique occurrence and differential geochemical characteristics are divided into three independent CO2 fluid recharge periods. Type I (hair-like) davisite represents the first recharge, and the fluid causes the most significant rare earth element migration; type II (needle-like) represents the second recharge, and the fluid action is relatively weak; type III (fine lath-like) represents the third recharge, and the fluid action intensity is between the first two periods. The trace elements and rare earth elements of the three occurrence types of davisite show obvious differences but remain consistent as a whole, and show a continuous paragenetic relationship, indicating that at least 3 periods of deep-source inorganic CO2 recharge occurred in the recharge area, and the entire recharge process is a continuous episodic recharge. This clarifies the multi-period, episodic and continuous CO2 fluid recharge law in the study area.

[0060] S4, based on the divided fluid recharge period, using geochemical methods, and matching the analysis results with regional tectonic characteristics and events, to determine the carbon source fluid recharge time window of CO2 tracer minerals in the study area:

[0061] Based on the three fluid charging phases divided by S3, geochemical methods were used to determine the possible formation temperature and time range of each phase: seismic profiles of the stratigraphic data of well Gu27 were calibrated according to the synthetic seismic record, and the erosion amount was calculated by truncating the time-depth converted seismic profile data. Thus, the burial / thermal history of well Gu27 was reconstructed using PetroMod software. Figure 13 By combining the homogenization temperatures (Th) of hydrocarbon inclusions in the aqueous solution of the soda ash sandstone, the hydrocarbon charging time was estimated. This method indicates that the entire hydrocarbon charging process occurred between 82 Ma and 65 Ma (i.e., the end of the open water period). The homogenization temperatures (92.8–97.3°C) of the four fluid inclusions in the soda ash may correspond to 73–67 Ma or 50–44 Ma. Petrological observations show that soda ash mainly fills the residual pores of the secondary enlarged rim of quartz, indicating that its precipitation is later than the main cementation period of quartz. Therefore, the charging of deep-source inorganic CO2 is later than the main period of hydrocarbon charging and the formation of the secondary enlarged rim of quartz. Therefore, based on the above analysis, the estimated reasonable CO2 charging time is approximately 50–44 Ma. To compensate for the lack of homogenization temperature data for soda ash, δ¹⁴Tc is used... 18 Ocarb values ​​are used to estimate the precipitation temperature of pyrope and dolomite. The pore water in the Quan 4 Member sandstone of the southern Fuxin Uplift belt mainly originates from freshwater (with a small amount of saline water mixed in), therefore the δ¹⁴ value of the pore water during pyrope precipitation is... 18 OSMOW is approximately -7.0‰. The precipitation temperature of sodium aluminum oxide was calculated using the dolomite-water distillation equation proposed by Juske (2014), and the results were 93.64 °C to 124.98 °C, corresponding to 65 Ma to 45 Ma.

[0062] Subsequently, the above geochemical analysis results were precisely matched with regional tectonic features and events to determine the charging time windows of carbon source fluids in each phase:

[0063] The first CO2 charging window (corresponding to type I diatomite in S3): The deep-source inorganic CO2 gas reservoir in the central depression of the Songliao Basin has been confirmed to be associated with tectonic inversion activity and Shuangliao volcanic activity. This tectonic inversion activity began at the end of the Mingshui period (65 Ma) and ceased at 60 Ma. This time window (65-60 Ma) corresponds to the aforementioned use of δ¹⁸O⁻. 18 The estimated Ocarb values ​​for the charge initiation time (65 Ma) are highly consistent. Therefore, the time window for the first CO2 charge is defined as 65–60 Ma.

[0064] The second CO2 charging time window (corresponding to type II davyne in S3): There is a lack of sedimentary records from the end of the Cretaceous to the middle Eocene in the Songliao Basin, indicating that the basin was in a stage of uplift and denudation during this period, making it difficult to determine the stop time of CO2 charging through stratigraphic records. Regionally, the collision between the Indian subcontinent and the Eurasian plate began in the early Eocene (56 Ma); at the same time, the Pacific plate was nearly vertically subducted to the Eurasian continent margin during 85-53 Ma. These intense tectonic activities may have had an important impact on the Songliao Basin, resulting in a high uplift and denudation rate. Therefore, the start time of the second CO2 charging was associated with the start time of the collision between the Indian and Eurasian plates (56 Ma), and the stop time was matched with the end of the Pacific plate subduction period (53 Ma), and the charging time window was determined to be 56-53 Ma.

[0065] The third CO2 charging time window (corresponding to type III davyne in S3): Recent studies have shown that the change in the direction of Pacific motion began at 50 Ma and lasted for about 8 Ma before it was finally completed, i.e., from (50 ± 0.9) Ma to (41.5 ± 0.3) Ma. At the same time, volcanic eruptions in the Shuangliao area occurred from 51 to 41 million years ago. These two major regional tectonic-magmatic events perfectly match the davyne formation time directly indicated by fluid inclusion homogenization temperatures (50-44 Ma). Therefore, the third CO2 charging time window was determined to be 50-44 Ma, and the end of the stratigraphic reaction time after the stop of the charging was set to 41 Ma.

[0066] Finally, by precisely matching the geochemical temperature constraints with regional tectonic events, the three periods of deep-source CO2 fluid charging in the study area were successfully determined to be: the first period 65-60 Ma, the second period 56-53 Ma, and the third period 50-44 Ma (reaction to 41 Ma).

[0067] It is to be noted that the step of estimating the hydrocarbon charging time by the uniform temperature (Th) value is specifically as follows: firstly, microthermometric analysis is conducted on the hydrocarbon inclusions and associated aqueous solution inclusions in the dawsonite-bearing sandstone to obtain a uniform temperature range of 92.8-97.3°C, which represents the minimum formation temperature when the hydrocarbon fluid is captured. Subsequently, based on the calibrated horizon data and the calculated denudation amount of the synthetic seismic record, the burial history and thermal evolution history of the target well are reconstructed by using the PetroMod software to obtain a continuous curve of the formation temperature changing with time. The measured inclusion uniform temperature is taken as a temperature constraint condition, and coupled analysis is conducted with the thermal history curve, and it is found that the temperature range corresponds to two possible time windows: 73-67 Ma or 50-44 Ma. In combination with the occurrence characteristics of the dawsonite filled in the residual pore of the quartz secondary enlargement edge in the petrological observation, it is indicated that the CO2 charging is later than the main stage of quartz cementation and the peak period of hydrocarbon charging, and thus the later 50-44 Ma is determined as the reasonable CO2 charging time.

[0068] S5, based on the carbon source fluid charging time, a dense sandstone reservoir model corresponding to the study area is constructed by using geochemical simulation software, and the dynamic change process of different CO2 tracer minerals under different period carbon source fluid charging conditions is simulated:

[0069] Model construction and initial condition setting: the geochemical simulation is conducted by using the GWB (The Geochemist's Workbench) software. Based on the three-period carbon source fluid charging time window determined in S4, a one-dimensional reaction and migration model corresponding to the dense sandstone reservoir in the study area is constructed. The model parameters are as follows: the average thickness of a single layer of sandstone is 20 m, the length in the horizontal direction (X axis) is 1000 m, and the model is divided into a grid shape with every 100 m in the horizontal direction and every 4 m in the vertical thickness direction. Referring to the reservoir physical properties in the study area, the initial porosity is set to be 18%. The initial mineral components are set to be quartz 35%, potassium feldspar 25%, plagioclase 11% (including sodium feldspar 2% and calcium feldspar 9%), montmorillonite 8.4%, and chlorite 2.4% according to the rock components of the normal area without CO2 charging. Figure 13 The corresponding ion components of the initial formation fluid are obtained by solute migration simulation (1 mol / L NaCl solution is stably balanced in the reservoir). The dissolution and precipitation kinetics parameters of the minerals are set according to the method of Xu et al. (2005, 2007) (Table 2), and the CO2 charging rate is set to be 0.1 mg / s according to the estimation of Goff et al. (2000), Werner & Brantley (2003) on hydrothermal and fracture channel CO2 discharge.

[0070] According to the charging time window determined in S4, three complete charging-reaction cycles are set to simulate the episodic charging process:

[0071] First cycle: 5 Ma (65-60 Ma) for injection, simulating CO2 injection; followed by 4 Ma (60-56 Ma) for formation reaction, simulating water-rock reaction after injection stopped.

[0072] Second cycle: 3 Ma (56-53 Ma) for injection; followed by 3 Ma (53-50 Ma) for formation reaction. The mineral assemblage and pore water chemistry at the end of the first injection-reaction cycle were used as initial conditions for this simulation.

[0073] Third cycle: 6 Ma (50-44 Ma) for injection; followed by 3 Ma (44-41 Ma) for formation reaction. The total simulation time was 24 Ma. Simulation results and dynamic process analysis:

[0074] The simulation results clearly reproduced the dynamic changes of different CO2 tracer minerals (mainly sodalite) and other authigenic minerals under the conditions of three-stage CO2 fluid injection.

[0075] First CO2 injection (65-60 Ma) and reaction (60-56 Ma):

[0076] Injection stage: CO2 injection caused a small increase in pH, followed by a sharp decrease to 3.03. Sodalite precipitated rapidly and in large quantities, with a peak precipitation of 2.522 x 10 8 mol (0.073% of the model volume), and slight dissolution at the end. Illite precipitated rapidly, and montmorillonite converted to illite. Potassium feldspar and calcium feldspar (especially calcium feldspar) dissolved vigorously. The porosity decreased slightly and then increased to 17.8. Reaction stage: After injection stopped, the pH increased to 3.4. The sodalite content first increased and then decreased, illite continued to form, and other minerals changed smoothly. The porosity increased slightly to 17.82.

[0077] Second CO2 injection (56-53 Ma) and reaction (53-50 Ma):

[0078] Injection stage: pH decreased to 2.42 again. The contents of sodalite and chlorite decreased significantly (dissolution), and illite continued to form slowly. The porosity first decreased and then increased, and the overall increased to 17.84. Reaction stage: The pH increased slightly to 2.47. The content of sodalite recovered (precipitation), and chlorite and montmorillonite continued to decrease. The porosity increased slightly to 17.86.

[0079] Third CO2 injection (50-44 Ma) and reaction (44-41 Ma):

[0080] Filling stage: the pH value dropped to the minimum 2.083. The content of davyne decreased sharply, chlorite was completely dissolved, illite and potassium feldspar changed slowly. The porosity dropped to 17.66. Reaction stage: the pH value rose slightly to 2.092. The content of davyne rose slightly, illite increased slowly. The porosity was basically stable at 17.65.

[0081] Simulation conclusion: Through the GWB numerical simulation, the dynamic formation and evolution process of davyne and other authigenic minerals in the reservoir under the condition of three-stage deep-source CO2 curtain filling in the study area was successfully reproduced. The simulation results and the petrological observation and geochemical characteristics of S1 to S3 were verified: the precipitation and dissolution of davyne are extremely sensitive to the filling activity of CO2, and the fluctuant change of its content (such as a large amount of precipitation in the first stage, and slight precipitation after dissolution in the last two stages) directly reflects the evolution of multi-stage fluid injection intensity, water-rock reaction degree and pore water chemical environment. The whole simulation dynamically reveals the whole process of CO2 fluid filling-rock response-pore evolution, and quantitatively supports the genetic model of "multi-stage curtain filling".

[0082]

Claims

1. A method for evaluating a deep source CO2 trace mineral formation process, characterized by, The method comprises the following steps: S1, by using petrological testing method, systematically characterize the occurrence characteristics of different deep source CO2 tracer minerals in the reservoir, determine the formation period of the CO2 tracer minerals, and infer the time sequence according to the occurrence characteristics; S2, based on the CO2 tracer minerals in S1, use carbon, oxygen and strontium isotope tests to clarify the element geochemical characteristics of different period CO2 tracer minerals, and identify the carbon source properties and genetic background; S3, by analyzing the vertical and horizontal distribution rules and geochemical characteristics of different CO2 tracer minerals, combining the time sequence in S1 and the genetic background in S2 for calibration, the CO2 tracer mineral fluid injection period and range are divided, and the injection rule is clarified; S4, based on the divided fluid injection period, using geochemical method, and matching the analysis results with regional tectonic characteristics and events, the carbon source fluid injection time window of the CO2 tracer minerals in the study area is determined; S5, using geochemical simulation software, based on the carbon source fluid injection time, a corresponding dense sandstone reservoir model of the study area is constructed, and the dynamic change process of different CO2 tracer minerals under different period carbon source fluid injection conditions is simulated.

2. The method of claim 1, wherein, The deep CO2 tracer minerals include davyne, ankerite and iron calcite.

3. The method of claim 1, wherein, The petrological testing method includes thin section observation, XRD clay mineral diffraction, scanning electron microscopy and cathodoluminescence analysis.

4. The method according to claim 1, characterized by, The geochemical characteristics are obtained by micro-area trace element test and rare earth element analysis.

5. The method of claim 1, characterized in that, The carbon, oxygen and strontium isotope test specifically includes: using stable isotope mass spectrometer to test the carbon and oxygen sources of CO2 tracer minerals, testing the strontium isotope ratio of davyne in the study area and comparing with the continental crust and lacustrine limestone.

6. The method of claim 1, characterized in that, The genetic background is determined by CO2-calcite / davyne fractionation coefficient calculation.

7. The method of claim 1, wherein, The geochemical method includes fluid inclusion homogenization temperature analysis and stratigraphic thermal burial history reconstruction method.

8. The method of claim 1, wherein, The geochemical simulation software uses Geochemist's Workbench.